Нове поховання з Китаївського курганного могильника: до дискусії про давньоруські квазікамери - Бібіков, Д.В.; Зоценко, І.В. (Археологія і давня історія України, 2022)
У 2021 р. на території Китаївського курганного некрополя авторами було виявлене інгумаційне
поховання в гробовищі, поміщеному до добре збереженої дубової камери. У статті аналізуються
конструктивні особливості захоронення, його датування та місце в схемі еволюції давньоруського
поховального обряду Х—ХІ ст. In 2021, on the territory of the second mound group
of the Kytaiv Cemetery on the outskirts of Kyiv the
authors discovered the inhumation burial in a coffin
placed in a wooden funeral chamber. Burials with
wooden structures made directly in the grave pit have
been widespread in Northern and Eastern Europe of
the Viking Age and are well known in the literature as
chamber burials. Some modern researchers distinguish
among the early medieval burials the category of socalled
«quasi-chambers» which are similar to original
chamber tombs but differ from them in certain important
structural and ritual elements. In our opinion, the
burial complexes, combining wooden walls and «movable
» coffin, as the one under discussion, should also be
included into this category. They differ from original
chambers by general semantics of the rite and usually
are later chronologically. In the 1910s and 1970s,
similar assemblages were excavated in the first barrow
group of the cemetery.
According to the grave goods the newly discovered
burial can be considered ordinary, and the mound over
the burial chamber is one of the smallest in the mound
group. Thus, at least in the territory of the Kyiv area
the chambers with coffins at the late 10th and early
11th centuries became a mass phenomenon, losing the
elitist character inherent in original chamber tombs.
Compared to the latter the design of burial structures
is also showing clear signs of simplification.
The obtained results prove the expediency of classification
the chambers with coffins as one of the types
of Old Rus quasi-chamber burials. Further theoretical
developments in this direction and new excavations
should complement the reconstructed vision of religious,
social and political progress of the population of
Old Rus at the stage of statehood formation.